EFFECTS OF CINNAMOMUM ZEYLANICUM BARK EXTRACT ON NOCICEPTION AND ANXIETY LIKE BEHAVIOR IN MICE - SEEMA JAIN; SPARSH GUPTA (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The aim of the study was to assess the effect of the extract of Cinnamomum zeylanicum (CZ) bark in the experimental models of pain and anxiety-like behavior in mice. Methods: The extract of CZ bark was administered at the doses of 100, 200, and 400 mg/kg, per orally (p.o) and morphine used as a positive control for pain models, was administered at the dose of 5 mg/kg, intraperitoneally (i.p.). Antinociceptive activity was evaluated using three experimental animal models of pain, namely, tail flick, hot plate, and formalin test. Elevated plus maze test was used to assess the effect on anxiety-like behavior. Rotarod apparatus and actophotometer were used to test muscle coordination and locomotor activity, respectively. Results: Administration of CZ bark extract in the dose of 200 and 400 mg/kg showed significantly increased in the tail-flick latency and latency to reaction time in hot plate test as compared to the control group. In the first phase (0–5 min) of the formalin test, a significant reduction in the pain response was found in CZ (200 and 400 mg/kg) and morphine-treated groups, however during the second phase (30–35 min) significant reduction in formalin-induced pain response was observed in 100, 200, and 400 mg/kg CZ extract-treated group when compared to control group. CZ extract administration at 200 and 400 mg/kg dose caused a significant increase in the percentage of time spent in open arms in the elevated plus maze as compared to the control group. Conclusion: Results suggest that CZ bark extract possesses the antinociceptive activity and modulates anxiety-like behavior.